Spatial Distribution Of The Michino (Manilkara Bidentata (A. DC) A. Chevalier), District Of Huarango, Province Of San Ignacio, Cajamarca, Peru (International Journal of Environmental Sciences, 2025)
The objective of this research was to evaluate the spatial distribution of the michino (Manilkara bidentata (A. DC) A. Chevalier) in the district of Huarango, San Ignacio, Cajamarca, Peru. The field work was carried out in nine sectors: Sábanas, El Acerillo, La Playa, Caña Brava, El Triunfo, La Laguna, El Derrumbo, Naranjos Chaca and La Totora, an inventory of the individuals was carried out, georeferencing, recording data such as CAP, HF, HT, shape and condition of the stem, crown shape and phenology; In addition, he collected samples for identification. The results were: 1144 individuals located in an altitudinal range between 700 - 1225 m s. n. m., the largest amount was found in the Sabanas sector with 309 individuals and in La Totora the lowest amount with 17 individuals. The registered diameters oscillated between 10 - 150 cm, the largest number of individuals were between 31 - 40 cm with 291 (26 %), followed by 269 individuals (23.5 %) between a range of 21 to 30 cm DAP, Likewise, the total height was recorded, where the largest number was found between 11 to 15 m with 561 individuals (49 %). Regarding its phenology, 30,16 % was found in flowering and 7,78 % in fruiting. The species was described, recording information on vegetative and reproductive organs, and the uses they give it in the study area.